Loss of neurofibromin Ras-GAP activity enhances the formation of cardiac blood islands in murine embryos - Yzaguirre, Amanda D (eLife, 2015)
Type I neurofibromatosis (NF1) is caused by mutations in the NF1 gene encoding neurofibromin. Neurofibromin exhibits Ras GTPase activating protein (Ras-GAP) activity that is thought to mediate cellular functions relevant to disease phenotypes. Loss of murine Nf1 results in embryonic lethality due to heart defects, while mice with monoallelic loss of function mutations or with tissue-specific inactivation have been used to model NF1. Here, we characterize previously unappreciated phenotypes in Nf1(-/-) embryos, which are inhibition of hemogenic endothelial specification in the dorsal aorta, enhanced yolk sac hematopoiesis, and exuberant cardiac blood island formation. We show that a missense mutation engineered into the active site of the Ras-GAP domain is sufficient to reproduce ectopic blood island formation, cardiac defects, and overgrowth of neural crest-derived structures seen in Nf1(-/-)embryos. These findings demonstrate a role for Ras-GAP activity in suppressing the hemogenic potential of the heart and restricting growth of neural crest-derived tissues. DOI: http://dx.doi.org/10.7554/eLife.07780.001